Towards developing a rhesus monkey model of early Alzheimer's disease focusing on women's health. Issue 11 (31st May 2021) - Beckman, Danielle; Morrison, John H.
Abstract: Alzheimer's disease (AD) is the most common cause of elderly dementia, affecting nearly 50 million people worldwide, with two‐thirds of the cases in the USA in women. Despite considerable investment, this prevalence is expected to increase further in the coming decades, based on the projected demographics of the population. Currently, most of the preclinical AD studies rely on transgenic mice carrying mutations associated with the early onset familiar form of AD, although the vast majority of cases are sporadic. A prevailing current hypothesis is that the cascade of events leading to AD starts with the accumulation of small soluble oligomers of the Aβ peptide (AβOs) that target and disrupt synapses. Taking advantage of the high translational power of rhesus monkeys due to their physiological and genetic similarities to humans, we recently developed a female rhesus monkey model of early AD pathogenesis based on exogenous administration AβOs. Here we review and discuss how soluble oligomers of Aβ can target vulnerable spines in the neocortex and hippocampus of female middle‐aged monkeys and induce neuroinflammatory responses, similar to what is known to occur in the human brain. Developing a rhesus monkey model of early AD focusing on women's health is critical for the understanding of how hormonal changes during menopause transition affect brain health and ultimately may contribute to AD neurodegeneration. Abstract : Oligomeric Aβ (red) act as synaptotoxins, targeting vulnerable spines in the female rhesus monkey brain and inducing microglia activation​ (dark blue). Research highlights: We recently described the development of a new female rhesus monkey model of Alzheimer's disease (AD) based on the infusion of exogenous soluble Aβ peptide (AβOs), that mimic the early stages of AD pathogenesis. Here we review and briefly discuss how AβOs can target the neocortex and hippocampus of female adult monkeys, similar to what is known to occur in the human brain. Developing a female rhesus monkey model of early AD focusing on women's health is critical for the understanding of how hormonal changes during menopause transition affect brain health and ultimately may contribute to AD neurodegeneration.